Structuring the message-passing channels - Chrobot, Stanisław; Stras, Agata; Stras, Robert (Zielona Góra: Uniwersytet Zielonogórski)
Low-level primitives for a high-level language and protocols in this language are proposed to implement synchronous message passing for a set of distributed processes running on a set of single-processor multiprocessing nodes. This implementation is meant to explicitly express process scheduling and message dispatching algorithms in the high-level language.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka